Linguistics and Its Role in the Production of Critical Terminology - chenene, kouider (El Omda in Linguistics and Discourse Analysis, 2018)
Our interest in this study is based on the term as a specific convention, meaning the agreement of a linguistic community to establish something and circulate it within the literature of writing. The Arabs gave this field great attention, focusing on formulating terms and distinguishing between their linguistic and technical meanings, due to its impact on general intellectual aspects. A term is a condensed representation of the organic relationship between the mind and language, and it is also connected to cognitive phenomena. In every branch of knowledge, terms serve as the central core from which the sphere of intellectual influence extends and through which intellectual orientation is consolidated.